Direct Constraints on Secondary HONO Production in Aged Wildfire Smoke From Airborne Measurements Over the Western US. Issue 15 (10th August 2022) - Peng, Qiaoyun; Palm, Brett B.; Fredrickson, Carley D.; Lee, Ben H.; Hall, Samuel R.; Ullmann, Kirk; Weinheimer, Andrew J.; Levin, Ezra; DeMott, Paul; Garofalo, Lauren A.; Pothier, Matson A.; Farmer, Delphine K.; et al.
Abstract: Nitrous acid (HONO) mixing ratios measured in aged wildfire smoke plumes were higher than expected from known homogeneous chemical reactions. In a representative smoke plume, intercepted hours to days downwind of the source, the missing HONO source was highly correlated to particulate nitrate photolysis and NO2 reactive uptake to particles. Using a multilinear regression involving these two sources, we could explain the missing HONO production in this plume ( R 2 = 0.77). The resulting fit parameters from this plume had good explanatory power ( R 2 = 0.64) for missing HONO production in other fire plumes. The mean enhancement factor for particulate nitrate photolysis relative to gas‐phase nitric acid photolysis was 63 and the mean NO2 reactive uptake coefficient to submicron aerosol surface area forming HONO was 4.9 × 10 −4 . Given the likelihood of other neglected secondary HONO sources, these values are upper‐limits, suggesting a need to revisit HONO formation mechanisms in aged wildfire smoke. Plain Language Summary: A river of smoke from multiple wildfires was sampled far downwind and served as a natural laboratory for evaluating sources of nitrous acid (HONO) in aged wildfire smoke. HONO photolysis is an important source of reactive oxidants that initiate chemical transformations of wildfire emissions. We demonstrate that sources of HONO from chemical processes, known as secondary HONO sources, can largely be explained by two processes – the photolysis of particulate nitrate and the reactive uptake of nitrogen dioxide (NO2 ) to smoke aerosol particles. High time resolution in situ observations of HONO and auxiliary measurements were used to map out variations in the missing HONO source across a wide span of wildfire characteristics. The results place an upper limit on the magnitude of HONO sources from particulate nitrate photolysis, and suggest that the heterogeneous NO2 reactive uptake to smoke particles could be more important than previous field studies have indicated. These findings demonstrate the existence of additional processes other than direct emissions responsible for HONO formation in fire smoke. This secondary HONO source could increase the oxidizing capacity of wildfire smoke plumes significantly downwind of the emission source and therefore affect the formation and lifetime of other secondary wildfire smoke components. Key Points: Secondary multi‐phase processes dominate daytime HONO levels in aged (>3 hr) fire smoke The inferred strength of secondary HONO production is most correlated to NO2, aerosol surface area, and particulate nitrate We find significantly weaker HONO formation from particulate nitrate photolysis than previous reports